2024
DOI: 10.1002/ame2.12392
|View full text |Cite
|
Sign up to set email alerts
|

Conditional knockout of the NSD2 gene in mouse intestinal epithelial cells inhibits colorectal cancer progression

Mengyuan Li,
Hanxue Chen,
Xingjiu Yang
et al.

Abstract: BackgroundNuclear receptor‐binding SET domain 2 (NSD2) is a histone methyltransferase, that catalyzes dimethylation of lysine 36 of histone 3 (H3K36me2) and is associated with active transcription of a series of genes. NSD2 is overexpressed in multiple types of solid human tumors and has been proven to be related to unfavorable prognosis in several types of tumors.MethodsWe established a mouse model in which the NSD2 gene was conditionally knocked out in intestinal epithelial cells. We used azoxymethane and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Further analysis revealed that a deficiency of NSD2 results in decreases of H3K36me2 at protein level and Fmo expression at mRNA level to impede taurine accumulation, both in vitro and in vivo. Several studies have shown the significant importance of NSD2 in chromatin regulation and regulates cell senescence, proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) 19,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] . Previous studies suggest that NSD2mediated H3K36me2 is crucial for transcription activation and the expression of multiple oncogenes in colorectal cancer (CRC) 25,30,37,38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis revealed that a deficiency of NSD2 results in decreases of H3K36me2 at protein level and Fmo expression at mRNA level to impede taurine accumulation, both in vitro and in vivo. Several studies have shown the significant importance of NSD2 in chromatin regulation and regulates cell senescence, proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) 19,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] . Previous studies suggest that NSD2mediated H3K36me2 is crucial for transcription activation and the expression of multiple oncogenes in colorectal cancer (CRC) 25,30,37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the significant importance of NSD2 in chromatin regulation and regulates cell senescence, proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) 19,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] . Previous studies suggest that NSD2mediated H3K36me2 is crucial for transcription activation and the expression of multiple oncogenes in colorectal cancer (CRC) 25,30,37,38 . These studies imply that NSD2, as a histone modifier, may play different roles depending on the genetic environment or context.…”
Section: Discussionmentioning
confidence: 99%